ФОРМУВАННЯ КОМУНІКАТИВНОЇ КУЛЬТУРИ МАЙБУТНІХ УЧИТЕЛІВ У ВИЩОМУ НАВЧАЛЬНОМУ ЗАКЛАДІ (Педагогіка вищої та середньої школи, 2022)
The article shows the necessity o f forming future teachers’ communicative culture in the conditions of higher educational establishment. It also deals with the ways and methods of solving the problem of forming communicative culture.